Peningkatan kemampuan koneksi matematis melalui model pembelajaran brain-based learning (BBL) pada siswa kelas VIII SMPN 7 Tambusai - Saufi, Yai Anggri; Deswita, Hera; Arcat (Karoteh Utama, 2020)
This study aims to determine whether there is an improvement in the mathematical connection abilities of eighth-grade students at SMP N 7 Tambusai through the Brain-Based Learning model. This quasi-experimental research uses a randomized control group pretest-posttest design. The population includes all eighth-grade students at SMP N 7 Tambusai. Samples were taken using simple random sampling, resulting in two classes as samples: class VIII A as the experimental group and class VIII B as the control group. The research instrument was a test of mathematical connection abilities. Data from the test results were analyzed to test the hypothesis. Before hypothesis testing, a prerequisite normality test using the Liliefors test was conducted, which showed that the data were not normally distributed. Subsequently, hypothesis testing was carried out using the Mann Whitney test. The results indicated that Zcount > Ztable​, specifically 3.40 > 1.96 for α = 0.05, leading to the rejection of H0. Thus, it can be concluded that there is an improvement in the mathematical connection abilities of eighth-grade students at SMP N 7 Tambusai through the Brain-Based Learning model in the 2019/2020 academic year.